Biodiversity and trophic relationships in some brackwish water ecosystems in West Africa - (:unkn) unknown (My University, 2004)
An Ecopath model of the Sine-Saloum estuary with a total of 37 functional groups is used inthis study to determine the key features of this aquatic system. The high fish species biodiversityin the ecosystem may play a role of assuring its integrity, especially in the presence of stress,though we observed that this is not entirely the case. Results show that another mitigating factoris the level of interaction strengths between functional groups. Stability is improved by moreweak connectance, as well as shorter and fatter pyramids. Though differing issues arise withrespect to questions driving a system’s stability, methods and approaches should considerplacing results in the context of a broader ecological theory.
Keywords: African Research